Association Between Air Pollution and Lung Lobar Emphysema in COPD - Tung, Nguyen Thanh; Ho, Shu-Chuan; Lu, Yueh-Hsun; Chen, Tzu-Tao; Lee, Kang-Yun; Chen, Kuan-Yuan; Wu, Chih-Da; Chung, Kian Fan; Kuo, Han-Pin; Thao, Huynh Nguyen Xuan; Dung, Hoang Ba; Thuy, Tran Phan Chung; et al. (Frontiers in Medicine, 2021)
The development of emphysema has been linked to air pollution; however, the association of air pollution with the extent of lobar emphysema remains unclear. This study examined the association of particulate matter <2.5 μm in aerodynamic diameters (PM2.5) (≤2.5 μm), nitrogen dioxide (NO2), and ozone (O3) level of exposure with the presence of emphysema in 86 patients with chronic obstructive pulmonary disease (COPD). Exposure to the air pollution estimated using the land-use regression model was associated with lung function, BODE (a body mass index, degree of obstruction, dyspnea severity, and exercise capacity index) quartiles, and emphysema measured as low-attenuation areas on high-resolution CT (HR-CT) lung scans. Using paraseptal emphysema as the reference group, we observed that a 1 ppb increase in O3 was associated with a 1.798-fold increased crude odds ratio of panlobular emphysema (p < 0.05). We observed that PM2.5 was associated with BODE quartiles, modified Medical Research Council (mMRC) dyspnea score, and exercise capacity (all p < 0.05). We found that PM2.5, NO2, and O3 were associated with an increased degree of upper lobe emphysema and lower lobe emphysema (all p < 0.05). Furthermore, we observed that an increase in PM2.5, NO2, and O3 was associated with greater increases in upper lobe emphysema than in lower lobe emphysema. In conclusion, exposure to O3 can be associated with a higher risk of panlobular emphysema than paraseptal emphysema in patients with COPD. Emphysema severity in lung lobes, especially the upper lobes, may be linked to air pollution exposure in COPD.